Формування громадянської ідентичності в закладах вищої освіти - Макарова, О. П.; Makarova, O. P.; ORCID: http://orcid.org/0000-0002-5480-5942 (Вчені записки ТНУ імені В.І. Вернадського. Сер.: Психологія. – 2020. – Т. 31 (70), № 3. - С. 153-157, 2020)
Визначено, що громадянська ідентичність є базовою сходинкою у структурі особистості, динаміка її формування забезпечується спеціальними психолого-педагогічним ресурсами, складається із програми і технологій формування даної якості на етапах підліткового та юнацького віку. Надано теоретичне дослідження громадянської ідентичності у міждисциплінарних напрямках. Розглянуто науково-педагогічну модель формування громадянської ідентичності здобувачів вищої освіти.

The formation of civic identity of the individual today is an urgent task of modernization of society and is a practical value for improving the quality of the educational process. The concept of development of Ukrainian society needs the support of programs for the formation of a civic nation and national identity. Modernity requires knowledge of basic sciences, education of all-Ukrainian identity, patriotism, citizenship, legal self-awareness, tolerance. On the other hand – systems of educational activities that determine the ability of the individual to learn, cooperate in learning and transforming the world around them. One of the important problems in this direction is the problem of forming a civic identity in young people. The main qualities of citizenship include: patriotism, obedience to the law, trust in government, responsibility for their own actions, discipline, self-esteem, respect for fellow citizens, active citizenship, a combination of patriotic and national feelings and more. Adolescence and adolescence are the most important stage in the formation of readiness for personal self-determination where the basic is self-awareness and worldview, developed holistic orientation. Despite the urgency of the problem of civic identity, during training, there are some contradictions between the growing need to keep in the development of civic identity of modern youth and insufficient use of psychological and pedagogical resources of higher and secondary vocational education to address this issue. There is a contradiction between the need for the formation and development of civic identity in young people and a certain lag in psychological and pedagogical practice in the development and implementation of theoretical models, programs and development of this quality in vocational education systems. The modern development of young men and women leads to significant difficulties in forming a civic position, so it is advisable to implement a new strategy of education and construction of civic identity as a basic prerequisite for strengthening statehood.

Определено, что гражданская идентичность является базовой ступенью в структуре личности, динамика ее формирования обеспечивается специальными психолого-педагогическими ресурсами, состоит из программы и технологий формирования данного качества на этапах подросткового и юношеского возраста. Представлено теоретическое исследование гражданской идентичности в междисциплинарных направлениях. Рассмотрена научно-педагогическая модель формирования гражданской идентичности соискателей высшего образования.
Formation of civic identity in higher education institutions
Макарова, О. П. Формування громадянської ідентичності в закладах вищої освіти / Макарова О. П. // Вчені записки ТНУ імені В.І. Вернадського. Сер.: Психологія. – 2020. – Т. 31 (70), № 3. - С. 153-157. - DOI: https://doi.org/10.32838/2709-3093/2020.3/26.
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; Освіта. Педагогіка. Education. Pedagogy. Образование. Педагогика; Україна. Ukraine. Украина; громадянська ідентичність; civic identity; гражданская идентичность; особистість; personality; личность; навчально-виховний процес; educational process; учебно-воспитательный процесс; патріотизм; patriotism; патриотизм; ідентичність; identity; идентичность; заклади вищої освіти; institutions of higher education; заведения высшего образования; формування